2013
DOI: 10.1177/1479164112465442
|View full text |Cite
|
Sign up to set email alerts
|

Association of sulphonylurea treatment with all-cause and cardiovascular mortality: A systematic review and meta-analysis of observational studies

Abstract: We conducted a meta-analysis of cohort and case-control studies to evaluate all-cause and cardiovascular (CV) mortality of patients with type 2 diabetes mellitus (T2DM) who received sulphonylurea (SU) treatment, when compared to any other diabetes treatment. Only studies reporting raw data on mortality during SU treatment were included. Data were combined using random-effects (RE) models. Unadjusted odds ratios (ORs) are presented. Of 4991 publication titles and abstracts reviewed, 20 studies (n = 551,912 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 69 publications
(93 reference statements)
4
42
0
3
Order By: Relevance
“…ORIGIN on the other hand provided evidence that insulin initiated early in the course of type-2 diabetes does not generally increased of hypoglycaemia [47]. Generally sulfonylurea are perceived to be associated with increased cardiovascular risk [85]. Interestingly, it was demonstrated that a specific sulfonylurea, glibenclamide (also known as glyburide), was associated with a lower risk of CV complications compared to treatment using metformin (belonging to the biguanide class) or rosiglitazone (thiazolidinedione class) in T2D [86].…”
Section: Resultsmentioning
confidence: 99%
“…ORIGIN on the other hand provided evidence that insulin initiated early in the course of type-2 diabetes does not generally increased of hypoglycaemia [47]. Generally sulfonylurea are perceived to be associated with increased cardiovascular risk [85]. Interestingly, it was demonstrated that a specific sulfonylurea, glibenclamide (also known as glyburide), was associated with a lower risk of CV complications compared to treatment using metformin (belonging to the biguanide class) or rosiglitazone (thiazolidinedione class) in T2D [86].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of similar channels in vascular tissue has raised concerns about the effects of some sulfonylureas on cardiac vascular tissue and adverse outcomes. 34,35 In contrast to metformin's insulin-sensitizing effects, the sulfonylureas address reduced b-cell function and stimulate insulin secretion providing a complimentary mechanism for glucose-lowering. They are cost-effective and have clinical trial evidence for reducing microvascular complications in type 2 diabetes (United Kingdom Prospective Diabetes Study), although the reduction in cardiovascular events was not significant.…”
Section: Sulfonylureasmentioning
confidence: 98%
“…La reciente disponibilidad de nuevos antidiabéticos como los inhibidores de dipeptidil-peptidasa-IV, los análogos del péptido similar al glucagón tipo 1 y los inhibidores del transportador de sodio-glucosa tipo 2, aunado a estudios que muestran un probable incremento del riesgo de la mortalidad cardiovascular y por todas las causas en los pacientes manejados con sulfonilurea 32 , está llevando a un cambio en las prácticas de prescripción 4 .…”
Section: Discussionunclassified